How Can the Implementation of Regenerative Strategies and Systems Between Land and Sea Benefit Kiribati in Terms of Health and Wellbeing? - Nawisielski, Danielle (Auckland University of Technology, 2024)
This thesis engages architectural methodologies to investigate and address the pressing climate challenges facing Kiribati, a small island nation in the Pacific Ocean. To effectively explore and respond to the climate crisis in Kiribati, it is imperative to first understand the challenges and issues confronting the nation, as well as the profound impacts these challenges have on both the community and the surrounding environment. Kiribati is particularly vulnerable to climate change, experiencing rising sea levels, increased frequency of extreme weather events, and environmental degradation, all of which threaten the livelihoods, health, and cultural integrity of its inhabitants. Architecture offers a unique lens through which we can identify opportunities to mitigate and adapt to climate change. By embracing regenerative strategies and systems, architecture can foster a symbiotic relationship between humans and the non-human elements of the environment, including natural ecosystems. This approach seeks to create a harmonious and sustainable living environment that nourishes both people and the ecological systems that they depend on. The research presented in this thesis is established on the practical application of regenerative systems and strategies tailored to the specific context of Kiribati, which is currently engaging with the adverse effects of climate change. This involves not only identifying and implementing strategies that address immediate challenges but also creating long-term opportunities for resilience and sustainability. The strategies proposed are designed to be adaptable to both the current environmental conditions and the ongoing changes that climate change is expected to bring. The aim is to enhance the capacity of Kiribati’s built environment to withstand and respond to climate impacts. Additionally, this research considers the broader implications of these strategies for mitigating climate change effects throughout Oceania, emphasizing the interconnectedness of environmental issues across the region. This thesis highlights the critical role that architecture can play in shaping a sustainable future for Kiribati. By integrating regenerative practices into architectural design and urban planning, we can create resilient environments that not only protect but also empower communities to thrive in the face of climate change. The findings of this research aim to contribute to a more comprehensive understanding of how architectural interventions can be a vital part of the solution to the climate crisis in Kiribati.